Application of Service-Oriented Architecture with Middleware at Bank XYZ to Implement the PDAM Payment - Halim, Abd.; Muhamad Isa, Sani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research presents a significant innovation in the era of digitalization, where Bank XYZ implements service-oriented architecture (SOA) using middleware to offer the PDAM (Regional Water Company) payment. The objective of this research is to enhance the efficiency of the payment process and provide better services to PDAM customers. The proposed method for implementing SOA is SOMA (Service Oriented Modelling Architecture), which serves as the foundation for optimizing service integration. Through requirement analysis, system design, implementation, and testing, this research ensures the functionality and reliability of the implemented payment system. The research results indicate that the implementation of SOA with middleware using the SOMA method has successfully improved the efficiency and quality of the PDAM payment services at Bank XYZ. This method represents the latest solution for complex systems, enabling PDAM customers to experience a more efficient and responsive payment process. This research makes a valuable contribution to improving the payment process and may serve as an inspiration for other banks in this digitalization era.